Leptomeningeal lipid storage patterns in Fabry disease - Elleder, M; Christomanou, H; Kustermann-Kuhn, B; Harzer, K (Acta neuropathologica, 1994)
We found two patterns of leptomeningeal storage that reflect two basic visceral storage patterns in Fabry disease. (i) A generalized-type leptomeningeal storage pattern, affecting all main leptomeningeal cell types (external arachnoideal epithelium, fibroblasts, vessel wall elements), was a consistent finding in three cases of classical generalized visceral phenotype. (ii) A localized leptomeningeal storage pattern was expressed, to a high degree, solely in the external arachnoidal epithelium; this pattern was found in one case with the variant visceral-restricted-type storage (confined to the cardiocytes). Thus, the external arachnoidal epithelium may be particularly susceptible to Fabry lipid storage, probably caused by a distinctly larger sustained lysosomal lipid load as compared to other cell types.
Keywords: Fabryho nemoc; Fabry Disease; Arachnoid; Male; Aged; lidé; mužské pohlaví; senioři; Epithelium; epitel; Humans; metabolismus lipidů; arachnoidea; Lipid Metabolism